Effects of advertising appeal and endorser's credibility on radio advertising effectiveness / Nurhidayah Awang Damit - Awang Damit, Nurhidayah (2016)
In this study, researcher is aim to investigate the radio advertising effectiveness in radio stations. This study will investigate the factors influencing the radio advertising effectiveness. Factors such as advertising appeal, endorser's credibility and creativity were represented for measuring the radio advertising effectiveness. The research findings suggest that Advertising Appeal and Endorser's Credibility influenced radio advertising effectiveness, while factor of Creativity shows not significant value which means it does not influence the effectiveness of radio advertising. This study shows which factors influence the radio advertising effectiveness and recommend the best strategy for radio stations to improve the radio advertisement in order to attract the potential customers in future.